Mobile people, mobile law expanding legal relations in a contracting world - Benda-Beckmann, Franz von 1941-2013; Benda-Beckmann, Keebet von 1946-2022; Griffiths, Anne M. O. 1953- (Routledge, 2016)
Demonstrating how users of law, who often operate in multi-sited situations, are forced to deal with increasingly complex legal circumstances, this volume focuses on political and social processes through which people appropriate, use and create legal forms in multiple legal settings. It provides new insights into social and political processes through which transnational law is locally appropriated by different actors and presents empirical studies of confrontation, adaptation, vernacularization and hybridization of law due to its transplantation across the borders of national states. The contributors offer insights into modern dynamics of legal change, challenging assumptions about increasing homogeneity in law, with a keen eye for the historical situations in which current legal changes stand.